School choice criteria: the case of Siauliai city - Masiliauskienė, Erika; Geležinienė, Renata; Šiaučiulienė, Rūta (Social Welfare: Interdisciplinary Approach, 2016)
The article deals with the research related to the school choice process, conducted by Lithuanian and foreign scholars. Qualitative research results are presented disclosing that the most significant school choice criteria are the reputation and location of the school. The section discussing empirical research results presents the content of these and other criteria, analyses their importance for school choice.